2009
DOI: 10.1038/oby.2009.102
|View full text |Cite
|
Sign up to set email alerts
|

Serum Bile Acids Are Higher in Humans With Prior Gastric Bypass: Potential Contribution to Improved Glucose and Lipid Metabolism

Abstract: The multifactorial mechanisms promoting weight loss and improved metabolism following Roux-en-Y gastric bypass (GB) surgery remain incompletely understood. Recent rodent studies suggest that bile acids can mediate energy homeostasis by activating the G-protein coupled receptor TGR5 and the type 2 thyroid hormone deiodinase. Altered gastrointestinal anatomy following GB could affect enterohepatic recirculation of bile acids. We assessed whether circulating bile acid concentrations differ in patients who previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
351
4
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 528 publications
(412 citation statements)
references
References 44 publications
31
351
4
12
Order By: Relevance
“…Bile acids have also been recognized as important modulators of whole-body metabolism, increasing energy expenditure and preventing obesity, insulin resistance, and hyperglycemia, during high-fat feeding in rodents (17,18). In humans, circulating bile acids levels correlate with measures of insulin sensitivity and it has been suggested that changes in bile acids metabolism could also contribute to improved metabolism post-RYGB (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bile acids have also been recognized as important modulators of whole-body metabolism, increasing energy expenditure and preventing obesity, insulin resistance, and hyperglycemia, during high-fat feeding in rodents (17,18). In humans, circulating bile acids levels correlate with measures of insulin sensitivity and it has been suggested that changes in bile acids metabolism could also contribute to improved metabolism post-RYGB (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Other plausible mechanisms for the improvement of glucose homeostasis after procedures that like DJB involve a bypass of the small intestine include: (1) alteration in gut microbiota (19,20); (2) bile acid perturbations (17,18); (3) changes in neuroendocrine signaling (21); and (4) alterations in putative gut factors regulated by the duodenum, that may be involved in the diabetic alterations of glucose homeostasis (''anti-incretin'' theory) (9,24). A recent study by Lam et al (7) demonstrates that duodenal-jejunal bypass surgery activates nutrient-sensing signals in the jejunum and rapidly lowers endogenous hepatic glucose production in nonobese rats with uncontrolled diabetes, suggesting a possible contribution of intestinal nutrient sensing to the glucose-lowering effects of bypass procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in bile acids strongly correlates with the improvement in glucose and lipid metabolism [28,29] . Interestingly, catheter-mediated bile diversion to the mid distal jejunum in rats induces weight loss, decreases adiposity, improves glucose tolerance, and increases circulating bile acids [30] .…”
Section: Effect Of Bile Acids On Lipid and Glucose Metabolismmentioning
confidence: 99%
“…The studies with BA sequestrant colesevelam, a high-capacity BA-binding polymer, in humans with T2DM show significant reduction in LDL cholesterol, fpG, and HbA1c (69,70). patti et al (71) have found an increase in fasting total serum BA and individual BA concentrations of taurodeoxycholic, glycocholic, glycochenodeoxycholic, and glycodeoxycholic acids levels 2-4 years after gastric bypass, as compared to nonoperated individuals matched for preoperative or current BMI. It was suggested that this increase in serum BA levels might contribute to observed improvement in insulin sensitivity, incretin secretion, and postprandial glycemia after gastric bypass.…”
Section: Bile Acidsmentioning
confidence: 99%